A new approach for detecting HPV DNA in cervical swabs: comparison of nucleic acid extraction with direct PCR - Fatih Çubuk; Muhammet Çağrı Yıldız; Fikrican Balcı; Ahmet İrgin; Savaş Aşkın; Ekrem Sağtaş; Sedat kaygusuz (Virology Journal, 2025)
Abstract Background Almost all cases of cervical cancer are associated with persistent high-risk HPV infection. WHO prioritizes primary HPV testing for cervical cancer screening. Cervical cancer screening programs require the ability to process a large number of samples in a simple and standardized manner and obtain reliable results. The workload, time, and cost associated with the number of samples to be processed encourage the development of alternative methods to the traditional nucleic acid extraction method for population-based screening. In this study, we aimed to compare the performance of a commercial pre-denaturation solution with nucleic acid extraction in HPV DNA detection by PCR in cervical swab samples. Methods The study was designed in two phases: an experimental phase and a clinical phase. A total of 1200 cervical swabs were included in the clinical phase of the study. Positive results were obtained in 143 (11.9%) samples by nucleic acid extraction and 137 (11.4%) samples by PharmaDirect. Discordant results were detected in 28 (2.3%) samples. Results PharmaDirect provided 88.1% sensitivity compared to nucleic acid extraction. PharmaDirect provided high sensitivity for HPV genotype 16 (92.3%) and relatively limited sensitivity for mixed genotype infections (73.7%). Conclusion This study demonstrates the potential of an alternative commercial pre-denaturation product that does not require nucleic acid extraction for HPV DNA detection in cervical swab samples. Such approaches may represent a useful alternative for population-based screening studies. Trial registration Not applicable.